Rhinacanthin C ameliorates hyperglycaemia, hyperlipidemia and pancreatic destruction in streptozotocin–nicotinamide induced adult male diabetic rats - Adam, S.H.; Giribabu, N.; Rao, P.V.; Sayem, A.S.M.; Arya, A.; Panichayupakaranant, P.; Korla, P.K.; Salleh, N. (Elsevier, 2016)
Effect of Rhinacanthin C on hyperglycaemia, hyperlipidemia and pancreatic dysfunction in diabetes was investigated. In-vitro effect of Rhinacanthin C on glucose uptake was studied in 3T3-L1 cell line. Meanwhile, in-vivo effect of 28-days treatment with 5 mg/kg/day or 20 mg/kg/day Rhinacanthin C was studied in streptozotocin–nicotinamide induced male diabetic rats. Following completion of treatment, fasting blood glucose (FBG), HbA1c, insulin and lipid profile levels were measured by biochemical assays. Histopathological changes in pancreas were observed by light microscopy while levels of pancreatic oxidative stress were determined by enzymatic assays. Expression of insulin, TNFα, Ikkβ and caspase-3 in pancreas were quantified by immunohistochemistry. Molecular docking was used to identify interactions between Rhinacathin C with SOD or GPx enzymes. Dose-dependent increase in glucose uptake was observed with increasing doses of Rhinacathin C. Plasma FBG, HbA1c and lipid profile except LDL levels and pancreatic malonaldehyde level were reduced but serum insulin and pancreatic anti-oxidative enzymes (SOD, CAT and GPx) levels were increased in diabetic rats receiving Rhinacanthin C treatment. Decreased pancreatic histopathological changes with higher pancreatic insulin and Glut-2 levels but lower TNFα, Ikkβ and caspase-3 levels were observed in diabetic rats receiving Rhinacanthin C (P<0.05 compared to non-treated diabetic rats). In diabetic rats which received Rhinacathin C, changes in the above parameters did not achieve the value in non-diabetic rats. Docking shows Rhinacathin C possesses high degree interactions with SOD and GPx. By possessing these effects, Rhinacanthin C could be used as agent to alleviate pancreatic and other complications in diabetes.